Does Fintech Usage Alter the Relationships Between Financial Literacy, Behaviour and Well-Being? Evidence from India - Prabhakaran, Shamli; Mynavathi L, (Organizations and Markets in Emerging Economies, 2025)
The emergence of fintech has rapidly transformed the way people manage their finances, yet its impact on personal financial outcomes remains relatively understudied. This study aims to examine how fintech usage (FTU) influences the relationship between financial literacy (FL) and financial well-being (FWB) through financial behaviour (FB) using a moderated mediation model. Using a proprietary dataset, the hypothesised relationships are analysed applying the PROCESS macro in IBM SPSS Statistics. The analysis reveals that FB is a partial mediator in the FL-FWB equation, while FTU negatively moderates the relationship between FL and FB. However, FTU does not significantly moderate the relationship between FL and FWB. The findings carry significant implications for policymakers and fintech service providers. Policymakers should strive to include a digital literacy component in financial education programs to better equip individuals to navigate today’s digitalised society, while fintech companies should focus on designing products that complement users’ FL and facilitate the adoption of financially healthy behaviours.
Keywords: Financial literacy; financial behaviour; fintech usage; financial well-being